Vantagens da utilização do processo BIM para projeto e fabricação de peças modulares para construções em madeira - Levandoski, Leila Cristina (2019)
Wood has been a raw material for buildings for a long time. Features such as thermal and acoustic insulation, and mechanical properties like compressive stress, traction and bending make wood an excellent choice for building construction. In addition, the automated manufacturing of wood products such as LVL, and the technique of cutting computerized numerical control (CNC) machines, facilitate the production of components. There was also a huge revolution in the way of designing, the graphic model is built from modeling information, through software. This process is called BIM abbreviation of the English term (building information modeling). This article aims to present the advantages of using BIM for design of modular parts.